Sandwich generation and the demographic change - Szukalski, Piotr (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
Sandwich generation is a term used to describe people at a specific stage of their life when they are in the same time responsible for helping their aged parents and their children who have young offspring and who need to be supported with child-care. The paper is aimed at description how demographic changes affect the mentioned above stage of life and is focused on changing demographics of two careers: career ofown aged parents carer and career of grandparent.